Pelaporan Corporate Social Responsibility Perbankan Syariah dalam Perspektif Shariah Enterprise Theory (SET) - Dori Novarela; Indah Mulia Sari (Jurnal Akuntansi dan Keuangan Islam, 2015)
This study aimed to capture the corporate social responsibility (CSR) reporting inIslamic banks in Indonesia in shariah enterprise theory (SET). The SET disclosureitems adopted from Meutia (2009) that showed by two accountability dimension, i.e.vertical accountability that directed to Allah swt, and horizontal accountability thatdirected to three parties i.e direct stakeholders (employee and customer), indirectstakeholders (community), and the universe.The data taken from annual report 2013,processed and analyzed by content analysis. The study found that Bank MuamalatIndonesia is a highest CSR disclosure from ten Islamic banks. For each detail SET,each banks showed the different result. All banks raise the maximum score for thevertical accountability for the highly disclosure